Telaah Nilai Kepastian dan Keadilan pada Regulasi Mahar dalam Pembangunan Hukum Keluarga - Murdiana, Elfa; Zulaikha, Siti; Mahmudah, Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2021)
Explicitly, a dowry is not found in the legal protection of marriage, but normatively it is read firmly in Chapter V articles 30 to 38 of the Compilation of Islamic Law. In Article 2 Paragraph 1 of Law No. 1 of 1974 concerning Marriage states that